A Maternal Wall for Refugees? Gender and Labor Market Establishment in Sweden - Grönlund, Anne; Nordlund, Madelene (Nordic Journal of Working Life Studies, 2022)
Using longitudinal register data, we examined gender patterns in the long-term labor market establishment of refugees (n ≈ 11,700) and Swedish-born individuals (n ≈ 109,000). The main question was whether refugee women face greater difficulties than men and if gender differences can be attributed to care responsibilities. With multinomial logistic regression, cox regressions, and individual fixed effects models, refugees were observed at age 29–30 in 1997, then followed to age 50. Results show that both among refugees and Swedish-born, establishment was a protracted and insecure process for women. Over time, women caught up with men but in terms of stable employment, gender gaps prevailed throughout the fertile period and parenthood was negatively related to long-term establishment prospects. Future research should move beyond the focus on labor market entry to capture the mechanisms behind long term insecurities. The timing of parenthood and the importance of adult education are of particular interest.